Treatment of Wastewater from Thermal Desorption for Remediation of Oil-Contaminated Soil by the Combination of Multiple Processes - Feng Xiao; Jun Yin; Dongsheng Shen; Ting Chen; Li Lv (Journal of Chemistry)
Thermal desorption (TD) is one of the methods commonly used to remediate contaminated soil. However, as water is the liquid adsorbent of the off-gas treatment system in the TD stage, the wastewater generated after multiple cycles in the TD stage has low biodegradability and contains complex organic pollutants. In addition to petroleum hydrocarbon, there are also a lot of ammonia, emulsified oil, phenols, aldehydes, and ketones. In this study, effective removal of contaminants was achieved using a combined process of demulsification and flocculation (DF), ammonia stripping (AS), Fenton oxidation (FO), and reverse osmosis (RO). The combined process was optimized, and the maximum chemical oxygen demand (COD), NH3-N, turbidity, and extractable petroleum hydrocarbons (EPH) removal efficiencies reached 93.3%, 79.8%, 97.6%, and 99.9%, respectively. The FO was the key process for the efficient removal of contaminants. Ultraviolet-visible (UV/Vis), excitation-emission matrix (EEM), fluorescence spectroscopy, and gas chromatography-mass spectroscopy (GC-MS) showed that refractory macromolecular organic pollutants in water were removed, especially aromatics, phenols, and conjugated aldehydes or conjugated ketones, and further ring cleavage of benzene rings and carbocycles with carbon double bonds was observed. The cost-benefit analysis of the combined process was also carried out. The operating cost was 8.73 US$/m3, indicating that the combined process involved moderate costs for recalcitrant wastewater treatment. No studies have been published on combined processes for the treatment of wastewater from TD for the remediation of oil-contaminated soils. Therefore, this study could provide fundamental information based on experimental results and guidelines for wastewater treatment in engineering applications.